Addressing the other woman : textual correspondences in feminist art and writing - Lamm, Kimberly (Rethinking art's histories., 2018)
This book analyses how three artists - Adrian Piper, Nancy Spero and Mary Kelly - worked with the visual dimensions of language in the 1960s and 1970s. These artists used text and images of writing to challenge female stereotypes, addressing viewers and asking them to participate in the project of imagining women beyond familiar words and images of subordination. The book explores this dimension of their work through the concept of 'the other woman', a utopian wish to reach women and correspond with them across similarities and differences. To make the artwork's aspirations more concrete, it p.